Addressing Issues and Challenges in Managing Migratory Tuna Resources in the Western and Central Pacific Ocean. Issue 1 (14th May 2021) - Zhao, Fang; Mapuru, David; Waxin, Marie-France; Prentice, Catherine; Scavarda, Annibal
Tuna resources in the Western and Central Pacific Ocean are the world's largest and most valuable fisheries of their type and are vital to the economy and the sustainable development of the region. However, the region witnesses a rapid decline in tuna resources and the depletion of species such as bigeye and yellowfin tunas, and overharvesting of the other species. This study investigated the collaborative management model used to manage migratory tuna resources. The study followed a case study design with a focus on the Western and Central Pacific Ocean Fisheries Commission. Forty interviews were conducted with key stakeholders. The findings indicated that six factors, namely, structure and size, self-interest, self-enforcement, leadership style, equality of power, and culture, affected significantly the outcomes of a collaborative management model. The findings also provide important insights on how the factors influenced the outcomes. The study contributes to a better understanding of international governance of common-pool resources (CPRs) and its challenges, and thus helps policymakers develop strategies for managing migratory fishing resources for the sake of economic viability and sustainability in the region.